Service Innovation and Public Service Quality: Evaluating the RUMAH LANGIT Educational Program in Sidenreng Rappang Regency - Aris Baharuddin; Rezal Hadi Basalamah; Andi Muhammad Rivai; Muhammad Novrizal Ramadhan (PINISI Discretion Review, 2026)
This research was conducted to examine the implementation of the RUMAH LANGIT service innovation program and to evaluate its contribution toward improving public service quality in Sidenreng Rappang Regency. Quantitative approaches were employed through questionnaire-based data collection involving respondents associated with program implementation. Findings demonstrate that implementation of service innovation was perceived positively based on dimensions consisting of relative advantage, compatibility, complexity, trialability, and observability. Assessment of public service quality also produced favorable results across tangible, reliability, responsiveness, assurance, and empathy indicators. Statistical analysis further confirmed that service innovation exerts a positive and significant influence on public service quality. Findings indicate that innovation-based educational services possess substantial potential in strengthening educational accessibility, improving institutional effectiveness, and increasing community satisfaction regarding public educational service delivery.